15-Deoxy-Δ12, 14-prostaglandin J2 as an electrophilic mediator. Issue 7 (3rd July 2015) - Shibata, Takahiro
Abstract: Lipid-derived electrophilic molecules are endogenously generated and are causally involved in many pathophysiological effects. Prostaglandin D2, a major cyclooxygenase product in a variety of tissues and cells, readily undergoes dehydration to yield the J-series PGs such as 15-deoxy-Δ 12, 14 -PGJ2 (15d-PGJ2 ). Because of the electrophilic α, β-unsaturated ketone moiety present in its cyclopentenone ring, 15d-PGJ2 acts as an endogenous electrophile. 15d-PGJ2 can covalently react via the Michael addition reaction with critical cellular nucleophiles, such as the free cysteine residues of proteins that play a key role in the regulation of the intracellular signaling pathways. Covalent modification of cellular proteins by 15d-PGJ2 may be one of the most important mechanisms by which 15d-PGJ2 induces many biological responses involved in the pathophysiological effects associated with inflammation. This current review is intended to provide a comprehensive summary of 15d-PGJ2 as an endogenous electrophilic mediator of biological activities. Graphical abstract: : 15-Deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ), a cyclopentenone-type PG metabolite of PGD2, acts as an endogenous electrophilic mediator.